Methodological аspects of Identifcation of Banking Crises - O. V. Lukacheva (Мир новой экономики, 2019)
The main drawback of the existing methods of identification of banking crises is their dependence on subjective expert judgments, in connection with which, databases on crises have differences in the date and duration of crisis episodes. However, there is a more objective way to do it — the use of the money market pressure index (MPI), based on the indicators provided by the statistical authorities. In his work, the author explored the von Hagen & Ho (2007) index method and Laeven & Valencia (2012) method, which includes evaluative judgment. The aim of our work was, on the example of the banking sector ofRussiafor 1998–2016, the identification of the most accurate and sensitive methodology for assessment of banking crises. This study was carried out in stages. First, it was supplemented Laeven &Valenciathe database on the crises inRussiafrom 2011 to 2016. Second, it was built the money market pressure index (MPI) for the Russian banking sector for the period 1998–2016. At the final stage, the author compared the crisis episodes, identified using these two methods, which simultaneously identify the crises of 1998 and 2009. However, the crisis of 2014–2016 was identified only by the Laeven & Valencia criteria. This discrepancy can be explained by the shortcomings of the index methodology, which does not take into account hidden guarantees and direct support from the state. Moreover, the hypothesis that the banking crisis took place in 2014–2016 was confirmed by the Demirgüç-Kunt & Detragiache criteria (2005), as well as the financial stress index proposed by ACRA (ACRA FSI RU). Thus, it can be concluded that it is most acceptable to use the Laeven & Valencia methods when identifying banking crises.